Food security in the story of the Prophet Ibrahim in the Holy Qur’an - A Contemporary Reading - Mohammed Mansour Mazroaa, Hatem (Edelweiss Applied Science and Technology, 2024)
The idea of this article appears in analyzing the positions related to food security in the story of Prophet Ibrahim in the Holy Quran, highlighting its importance in reaching the overall landmarks related to food security in the Quranic approach, and the practical realistic applications associated with it. The article examines the issue of food security in the story of Prophet Ibrahim in verses from Surahs: Al-Baqarah, Hud, Ibrahim, and Adh-Dhariyat, as well as comparing between the stories of Prophet Ibrahim and Prophet Yūsuf in the same matter. This article has yielded several results, including the contexts that included food security positions in the story of Prophet Ibrahim in the Holy Quran being confined to the context of Allah’s selection of Prophet Ibrahim, the call to monotheism and establishing religion, the context of honoring guests, and the centrality of the issue of food security in the Holy Quran. Therefore it has been indicated by its diverse presence in Meccan and Medinan Surahs, and the integrated concept of achieving food security in the stories of the prophets in the Holy Quran; it has included the belief aspect, the ethical aspect represented in some positions in the story of Prophet Ibrahim, and the practical aspect represented in the story of Prophet Yūsuf.